Analisis Peranan Kepemimpinan VVC Plus dalam Meningkatkan Motivasi Kerja Pegawai - Totok Sasongko (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The aim of this research is that to know whether VVC plus leadership concepts are able to increase officials’ work motivation at officials Government of Education, Youth and Sport in Sanggau Regency and what the most dominant factor among those leadership concept on officials’ work motivation. The research’s population is the officials of official Government of Education, Youth and Sport in Sanggau Regency who are 32 people. All of them were being observed as sample or respondents for this research.The data is analysed by using double correlation and the finding is that there is a significant relationship among VVC plus leadership (Vision Change (X1), Value (X2), Courage (X3), Completency (X4), and strong character (X5) on work motivation (Y). it means that, the efforts to increase work motivation can be executed by increasing or applying VVC plus concept well. A competency variable (X4) is the most dominant factor on work motivation (Y) than other variables.Keywords: VVC Plus, Vision, Value, Courage, Strong Character Competency, Motivation.